Analisis Implementasi Nilai-Nilai Budaya Hukum dalam Kehidupan Berbangsa dan Bernegara: Studi Kritis Pendekatan Masyarakat, Budaya dan Hukum - Syafri Hariansah (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
This reseaech adressing to theoretically examine the correlation between society, culture and law in the dimensions of theory and practice. Law as a manifestation of cultural products is actually a guide for the community in living social life. Therefore, the statement of law as a cultural product is certainly in line with Rescoe Pound's view of the main purpose of law is tool of social engineering. In addition Friedman's legal system theory is one of the analytical tools in answering the concrete legal phenomena that happening in society. In general, this study uses a socio-legal approach, namely by trying to understand law as a form of social phenomenon. The socio-legal approach in this method is used as an effort to carry out a deepening of all aspects of legal formation to the implementation of the law itself in society. The outcome of this research demonstrate that cultural and legal society are 3 aspects inseparable from each other. Social interaction in society producess to culture, while law is the work of a cultured society. In everyday life, people's attitudes and behavior can influence or shape the perception of the law itself.